Dirasat in Economics and Business ABSTRACT NEW APPROACHES IN COMPARATIVE POLITICS - MOGHERBI, Dr. MOHAMED ZAHI (Dirasat in Economics and Business, 1979)
The comparative method is one of the main methods utili zed by most social scientists. It is also used in the sub-fields of political science. However, “.... among the several fields or subdisciplines into which the discipline of political science is usually divided, comparative politics is the only one that carries a methodological instead of a substantive label. The term 'com parative politics' indicates the how but does not specify the what of the analysis. The label is somewhat misleading because both explicit methodological concern and implicit methodologi cal awareness among students of comparative politics have gene rally not been very high.” (1) The objective of this study is to introduce the Arab reader, in some depth, to some of the new approaches in comparative politics which attempt to be more comparative in the real sense of the word. Two approaches ( Systems Approach and the Functional Approach ) are selected because of their great im pact on the development of comaparative politics.